Analisis Usaha Rumah Tangga Kerupuk di Desa Pasar Pedati Kecamatan Pondok Kelapa Kabupaten Bengkulu Tengah (studi kasus : Kerupuk Lia Jaya di Desa Pasar Pedati Kecamatan Pondok Kelapa Kabupaten Bengkulu Tengah) - Al Fajri Saputra; Andi Irawan; Reswita Reswita (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to determine the cost of production and operating profit obtained by the Lia Jaya cracker business in Pasar Pedati Village, Pondok Kelapa District, Central Bengkulu Regency in January 2021. This research was carried out on January 1-30 2021 at the Lia Jaya cracker business. The data taken is the production period data in January 2021. This research is an analysis using the analysis of the cost of production using the full costing method and the calculation of profit and loss, then the data obtained is analyzed quantitatively and qualitatively. The results showed that the total cost of production was Rp. 185.652. or an average of Rp. 27,545/Kg. The cost of production of tofu crackers is Rp.45,903,570 or Rp.27,162/kg. The cost of production for making firecracker sticks is Rp.23,844,357 or Rp.28,728/kg. The cost of production for making interlace crackers is Rp.23,358,328 or Rp.27,161/Kg. The cost of producing tempe crackers is Rp. 21,201,501 or Rp. 26,502/Kg. Macaroni is Rp. 24,387,595 or Rp. 28,691/Kg. The cost of production of jengkol crackers is Rp. 23,087,595 or Rp. 27,162/Kg. And the cost of production of fish crackers is Rp.23,869,661 or Rp.27,555/Kg. And Lia Jaya's cracker business made a profit of Rp. 18,380.003 with the proportion of profits for tofu crackers of Rp. 6,837,467, firecracker sticks of Rp. 509,948, interlocking crackers of Rp.2,617,563, tempeh crackers of Rp.2,2857,145, macaroni of Rp.732. 930, jengkol crackers Rp. 2,779,204, fish crackers Rp. 2,045,746.